Primary Spinal Germ Cell Tumors: A Case Analysis and Review of Treatment Paradigms. (7th November 2013) - Loya, Joshua J.; Jung, Henry; Temmins, Caroline; Cho, Nam; Singh, Harminder
Abstract : Objective . Primary intramedullary spinal germ cell tumors are exceedingly rare. As such, there are no established treatment paradigms. We describe our management for spinal germ cell tumors and a review of the literature. Clinical Presentation . We describe the case of a 45-year-old man with progressive lower extremity weakness and sensory deficits. He was found to have enhancing intramedullary mass lesions in the thoracic spinal cord, and pathology was consistent with an intramedullary germ cell tumor. A video presentation of the case and surgical approach is provided. Conclusion . As spinal cord germinomas are highly sensitive to radiation and chemotherapy, a patient can be spared radical surgery. Diverse treatment approaches exist across institutions. We advocate biopsy followed by local radiation, with or without adjuvant chemotherapy, as the optimal treatment for these tumors. Histological findings have prognostic value if syncytiotrophoblastic giant cells (STGCs) are found, which are associated with a higher rate of recurrence. The recurrence rate in STGC-positive spinal germinomas is 33% (2/6), whereas it is only 8% in STGC-negative tumors (2/24). We advocate limited volume radiotherapy combined with systemic chemotherapy in patients with high risk of recurrence. To reduce endocrine and neurocognitive side effects, cranio-spinal radiation should be used as a last resort in patients with recurrence.